2011
DOI: 10.1016/j.physletb.2011.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of final state interactions on charge separation in relativistic heavy ion collisions

Abstract: Charge separation is an important consequence of the Chiral Magnetic Effect. Within the framework of a multi-phase transport model, the effects of final state interactions on initial charge separation are studied. We demonstrate that charge separation can be significantly reduced by the evolution of the Quark-Gluon Plasma produced in relativistic heavy ion collisions. Hadronization and resonance decay can also affect charge separation. Moreover, our results show that the Chiral Magnetic Effect leads to the mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 59 publications
9
82
0
Order By: Relevance
“…The AMPT model is a useful tool for this study because it can mostly reproduce elliptic flow data, it includes decays of resonances possessing anisotropic flow, and it should contain correlations caused by momentum and local charge conservations. The AMPT results indeed show a linear dependence between the same-sign charge correlations and the elliptic anisotropy [41], qualitatively consistent with data. It is possible that the linear dependence observed in AMPT is due to the net effect of elliptic anisotropy and a difference between the same-and opposite-sign charged particle correlations [28,29].…”
Section: -13supporting
confidence: 86%
See 1 more Smart Citation
“…The AMPT model is a useful tool for this study because it can mostly reproduce elliptic flow data, it includes decays of resonances possessing anisotropic flow, and it should contain correlations caused by momentum and local charge conservations. The AMPT results indeed show a linear dependence between the same-sign charge correlations and the elliptic anisotropy [41], qualitatively consistent with data. It is possible that the linear dependence observed in AMPT is due to the net effect of elliptic anisotropy and a difference between the same-and opposite-sign charged particle correlations [28,29].…”
Section: -13supporting
confidence: 86%
“…The weaker dependence of the opposite-sign correlation on event anisotropy may be the net effect of two competing mechanisms of momentum and local charge conservations. Charge correlations as a function of elliptic anisotropy have also been studied in a multi-phase transport (AMPT) model [41], motivated by phenomenological studies [28,29,39] and the preliminary version of the data reported here. The AMPT model is a useful tool for this study because it can mostly reproduce elliptic flow data, it includes decays of resonances possessing anisotropic flow, and it should contain correlations caused by momentum and local charge conservations.…”
Section: -13mentioning
confidence: 99%
“…The TMC always gives negative contributions to both γ and δ, and it becomes more important for more peripheral collisions because the multiplicity decreases and v 2 increases as the centrality decreases. The TMC can give a large amount of contribution to γ αβ and δ αβ as shown by AMPT simulation [230,237] (This can also be roughly estimated by choosing v 2 ∼ 0.1 and N ∼ 1000 for moderate centrality bins at RHIC which gives γ TMC ∼ 10 −4 and δ TMC ∼ 10 −3 being at the same order of magnitude as the STAR results [211,212]). In order to evidence the contributions of CME, it is useful to subtract the TMC contribution from γ.…”
Section: A the Charge-dependent Azimuthal Correlation And Chiral Magmentioning
confidence: 83%
“…So far these experimental measurements of cos(φ α ± φ β ) are qualitatively consistent with the CME expectations. Recently, a multiphase transport (AMPT) model was implemented to study charge azimuthal correlations by introducing an initial electric charge dipole distribution, which discloses that final state interactions can play a significant role in weakening the initial charge separation in Au+Au collisions at the top RHIC energy [13]. An A ch -dependent charge asymmetry of pion elliptic flow is also reproduced by introducing an initial electric charge quadrupole distribution, which provides a helpful constraint to the quadrupole effect from the chiral magnetic wave [14].…”
mentioning
confidence: 99%
“…Nevertheless, no real dynamical scenario of metastable domains were taken into account in Ref. [13], because the imported dipole charge separation was assumed to be randomly distributed in the global fireball. In this work, we introduce initial separated charges located inside many P-or CP-odd bubbles, then some useful information about the properties of metastable domains is extracted by comparing charge azimuth angle correlations between the model and the experimental data.…”
mentioning
confidence: 99%